Pengaruh Motivasi, Lingkungan Kerja, dan Budaya Organisasi terhadap Kinerja Pegawai Melalui Kepuasan Kerja sebagai Variabel Mediasi (Kajian Studi Literatur Manajemen Sumber Daya Manusia) - Gradiana Bili, Maria; EHJ FoEh, John; A. Manafe, Henny; Man, Stanis (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
Performance management is the overall activity carried out to improve company performance, work group performance and employee performance in a company. This article only analyzes employee performance in terms of three factors, namely competence, work environment and leadership and job satisfaction as mediating variables through a review of literature studies. The results of the review of this article's literature study are as follows: 1. Competence affects job satisfaction; 2. The work environment influences job satisfaction; 3. Leadership influences job satisfaction; 4. Competence affects employee performance; 5. The work environment influences employee performance; 6. Leadership influences performance; 7. Competence, Work Environment and Leadership simultaneously influence employee performance; 8. Job satisfaction affects employee performance; 9. Job satisfaction mediates competency on employee performance; 10. Job satisfaction mediates the work environment on employee performance; 11. Job satisfaction mediates leadership on employee performance.